Antimony deposits in the Variscan Armorican belt, a link with mafic intrusives?. (16th February 2016) - Pochon, Anthony; Gapais, Denis; Gloaguen, Eric; Gumiaux, Charles; Branquet, Yannick; Cagnard, Florence; Martelet, Guillaume
Abstract: The Variscan Armorican belt was the World leading producer of antimony at the beginning of the twentieth century. However, geological controls on the deposits remain unconstrained. Here, we illustrate the field setting of mineralisations and perform a statistical analysis using Geographical Information System software, geophysical and geological data. The analysis shows that Sb deposits are spatially correlated with high‐density and magnetic zones. This may reflect the presence of mafic/ultramafic bodies at depth – a suggestion that is further supported by numerous occurrences of doleritic dykes throughout the region. Future antimony prospecting should focus on the high‐density and high‐magnetic zones which comprise about 18% of the Armorican massif. Links between Sb deposits and mafic intrusions are recognised elsewhere in the West European Variscan belt, emphasising that these may be key for antimony prospecting in deformation belts.